THE ROLE OF INTERNAL SUPERVISION IN REPOSITIONING SECONDARY SCHOOL ADMINISTRATION IN ENUGU STATE, NIGERIA - Amaka Onu, Eucharia; Omeke, Faith; Ozioko, Agatha; Edikpa, Edith (International Journal of Psychosocial Rehabilitation, 2024)
The study investigated the role of internal supervision in repositioning secondary school administration in Enugu State, Nigeria. A descriptive survey design was adopted for the study. The population of the study consists of 92 teachers from the selected 25 secondary schools in Nsukka education zone, Enugu state. Purposive sampling technique was adapted to the study. A sample size of 78 teachers was used because most of the teachers were on leave. A wellstructured Questionnaire titled the role of internal supervision in repositioning secondary school administration in Enugu state (QRISRSSA) containing 17 items were the instrument for data collection. The instrument was validated by three experts from the University of Nigeria, Nsukka. The validated instrument was trial tested, using 20 respondents which comprised of 15 female teachers and 5 male teachers outside the study area. Cronbach alpha method was used to determine the internal consistency of the instrument which gave overall reliability of 0.81. Mean and standard deviation were used in data analysis. The study revealed that the school administrators should endeavor to involve in thorough evaluation and monitoring of the school academic performance of the students, supervision of instructional delivery of the teachers, teachers and the no-tutorial staffs should be motivated as when due, and provision of quality instructional materials for effective teaching and learning should be taken into consideration. Based on the findings, it was recommended among others that the school administrators in sukka education zone should organize seminars, symposium, conferences and workshop in order to sensitize the staff on the relevance of internal supervision in circular schools.